Dicionário Estocástico Multipulso para Codificadores CELPDOI: 10.14209/jcis.1998.3 - Martins da Silva, Lúcio; Alcaim, Abraham (Journal of Communication and Information Systems, 2015)
This paper presents a new algorithm to design codebooks of sparse vectors for code excited linear prediction (CELP) speech encoders. The algorithm is based on multipulse excitations and on the LBG codebook training algorithm. The codebooks, which are referred to as multi pulse (MP) codebooks, have the inherent advantages of sparse codebooks. Moreover, they can be optimized by a closed-loop training procedure. We present a comparative analysis of the MP codebook with vector-sum (VS) and Gaussian codebooks. Simulation results show that the MP codebook yields the best performance in terms of speech quality. Complexities of these codebooks are also compared.